The Impact of Implementing Blockchain Technology in Learning on Data Security and Integrity - Iwan Adhicandra; Faiz Muqorrir Kaaffah; Chandra Halim Maharaja; Sabri Sabri (Journal of Computer Science Advancements, 2024)
The application of blockchain technology in learning has great potential to improve data security and integrity. Because blockchain is a decentralized technology that uses block chains to record and secure transactions in a transparent and permanent manner, it offers an excellent solution to address security and data integrity issues. This research was conducted with the aim of improving the security and integrity of student data. Student data can be stored in a distributed manner with blockchain. No one can change or delete it without their permission. This goal also includes increasing transparency and accountability of the learning process to ensure that the data used in the learning process is accurate data. The method used in this research is a quantitative method. This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. From this research carried out, researchers can obtain research results that blockchain technology is used to protect educational data by locking the learning history of the learning management system (LMS), so that assessments can be carried out effectively and allow all parties involved to access and verify information safely while ensuring data integrity and validity. Based on the results of this research, it can be concluded that the application of blockchain technology can help improve the security and integrity of student data, such as academic, financial and personal data, in the learning context. By using blockchain, students have complete control over their data and ensure that bad people cannot misuse or access it. Apart from that, blockchain technology can also increase transparency and accountability in the classroom.